Implementation of computational experiments on the study of celestial mechanics based on the energy approach - Мукушев , Б.; Мукушев , А. Б.; Таширова , М. Б.; Аширбаева , Д. Н.; Калхаман , К. С.; Салмырза , Г. Ж.; Сахиева , С. М. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
The article is devoted to the disclosure of the advantages of computational physics methods. One of these important methods is computer (or computational) experiments. The energy characteristics of celestial bodies were studied by means of computational experiments in the Mathcad application software package environment. The article presents graphical interpretations of the potential energy of interaction between a planet and a body, the Earth-Moon system and a spacecraft, and the potential of the Solar System. Therehave been createdtwo-dimensional and three-dimensional graphs of the potential energy of space systems consisting of two or more celestial bodies.